LEARNING FROM THE PRESENT AND THE PAST: A CONTEMPORARY AND HISTORICAL REVIEW OF AGRICULTURAL IMPACTS ON SOIL FERTILITY - Leslie Campbell (AGRICA, 2011)
Conventional farming involves the use of synthetic and chemical pesticides that increases the short-term productivity of the soil with the expense of its long-term fertility. The emergence of alternative agriculture movement is estimated to have become a progressive response in increasing awareness of the long adverse effects on an effort to promote the soil which is well cultivated by the agro-ecological environment. Although it is a shift from conventional farming, alternative farming practices have not been adequately integrated as organic farming techniques and remain non-organic farming options. In an effort to explore the differences, we conducted a literature review of temperate areas studies comparing to conventional and alternative farming techniques in terms of their effects on soil nutrient levels. This review was found that 70% of the literature supports the use of alternative techniques as the means of reducing the agriculture impact on fertility and health of the soil and highlights the need of further research on the topic of longitudinal studies primarily in the context of the ecology of temperate climate. To contextualize contemporary view with the developing popularity of the alternative conventional farming system, we also explored the literature about the impact of agriculture that expanded again from the 1920s. The historical study examined literature concerning long-term fertility soil in Canada Journal on scientific agriculture to capture general environment narration about alternative farming at that time. It was found that a segment of the pre-1950s literature viewed the farming practices sustainable time, citing the declining yields to support this claim. The latest increasing proved in alternative farming techniques in response to a growing awareness of the long-term effects of conventional farming can be contextualized in the context of history as well as the rise of a more traditional approach to farming.